Análisis, diseño e implementación del módulo: Voto electrónico, acoplado al sistema integrado Siutmach de la Universidad Técnica de Machala, empleando la metodología ICONIX, durante el período 2012 - Chuchuca Balladolid, Tania Mariuxi (2014)
The Technical University of Machala Education Unit still a higher level training in the province of El Oro, given the need to prioritize the academic progress has been chosen to implement this project called "Electronic Voting", which was developed with the to involve the University society to the use of technology we have in our midst and then stop using the typical physical paper, using a reliable, auditable, fast and timely system for the sole purpose of getting to set a different culture society.